Isolation and Identification of Endophytic Fungi in Cocoa Seedlings (Theobroma cacao L.) - Sepsriyanti Kannapadang; Dewi Fitrianti (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2024)
Endophytic fungi are organisms that infect healthy plant tissue without causing visible symptoms. This study aimed to determine the presence of endophytic fungi in cocoa plants following the application of boron and sodium hypochlorite. The research was conducted at the Screen House of the Faculty of Agriculture at Hasanuddin University and continued at the Disease Laboratory within the Department of Pest and Plant Disease Science, also at Hasanuddin University, from October 6, 2013, to March 15, 2014. Boron was applied to the plants in three treatments: Treatment A received 1 gram of boron, Treatment B received 0.5 grams of boron, and Treatment C served as the control group with no boron applied. Additionally, the plants were treated with sodium hypochlorite, which was sterilized for 5 minutes before the identification process to characterize the fungi. The results indicated that three genera of endophytic fungi were isolated from the cocoa plant stems following the application of boron: Aspergillus sp., Trichoderma sp., and Colletotrichum sp. Furthermore, one endophytic fungus, Rhizoctonia sp., was isolated from the cocoa stems after applying sodium hypochlorite.